Skin tear prevalence and associated factors: a systematic review - Kelly Cristina Strazzieri-Pulido; Giovana Ribau Picolo Peres; Ticiane Carolina Gonçalves Faustino Campanili; Vera Lúcia Conceição de Gouveia Santos (SciELO, 2015)
OBJECTIVETo identify and analyse skin tear prevalence and factors associated with its occurrence.METHODSystematic review of literature of studies published until June 2014 including studies published in full in English, Spanish or Portuguese. The studies were analysed according to the Strengthening the Reporting of Observational Studies in Epidemiology and the Guidelines for Critically Appraising Studies of Prevalence or Incidence of a Health Problem.RESULTSThe analysis of eight studies showed skin tear prevalence of 3.3% to 22% in the hospital setting and 5.5% to 19.5% in homecare. Advanced age, dependence on basic activities of daily life, frail elderly, level of mobility, agitated behavior, non-responsiveness, greater risk for concurrent development of pressure ulcers, cognitive impairment, spasticity and photoaging were cited as risk factors.CONCLUSIONSkin tear prevalence ranged from 3.3% to 22% and is mainly associated with advanced age and dependence on basic activities of daily life.